2001
DOI: 10.1002/jcu.1057
|View full text |Cite
|
Sign up to set email alerts
|

Development of intrahepatic arterial shunts in a transplanted liver: A potential pitfall for Doppler sonography

Abstract: We describe the hemodynamic features and anatomic basis of false-negative Doppler sonographic findings compared with angiographic findings in a 42-year-old woman after orthotopic liver transplantation complicated by hepatic artery thrombosis. Complete common hepatic artery thrombosis was demonstrated by Doppler sonography and digital subtraction angiography (DSA) on the first postoperative day. A thrombectomy was performed. DSA on the third day after transplantation again showed occlusion of the left hepatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Each extra anastomosis was associated with an approximately 2‐fold increased risk of E‐HAT. The other findings from the logistic regression concerning previous HAT and a small donor weight appear to be logical and in agreement with the literature . We advise routine daily monitoring of the arterial flow by Doppler US in the early postoperative period in the presence of 1 or both of these risk factors.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Each extra anastomosis was associated with an approximately 2‐fold increased risk of E‐HAT. The other findings from the logistic regression concerning previous HAT and a small donor weight appear to be logical and in agreement with the literature . We advise routine daily monitoring of the arterial flow by Doppler US in the early postoperative period in the presence of 1 or both of these risk factors.…”
Section: Discussionsupporting
confidence: 87%
“…At our unit, the management of E‐HAT depends on hepatic ischemic changes detected on scans and the degree of deranged liver transaminases. Early cases with an unaffected hepatic parenchyma and normal transaminases were considered for urgent relaparotomy and revascularization, and there were excellent outcomes for both adults and children (4 cases in our series with a success rate of 75%). De Gaetano et al, Langnas et al, and Pinna et al have reported that prompt revascularization (either surgical or radiological) decreases the need for retransplantation in E‐HAT cases.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In addition, hepatic perfusion may be abnormal 10 days after transplantation given changes in vascularization and development of portosystemic shunting. 31,32 It is also unclear in this liver transplant study whether residual cyclosporine, which could potentially compete with midazolam for CYP3A enzymes in vitro, may have been present in liver biopsy samples.…”
Section: A Sampling Of Studies Assessing the Validity Of Midazolam Asmentioning
confidence: 89%